Sensitivity and stability analysis of power system frequency response considering demand response and virtual inertia. Issue 6 (30th January 2020) - Saeed Uz Zaman, Muhammad; Bukhari, Syed Basit Ali; Haider, Raza; Khan, Muhammad Omer; Baloch, Shazia; Kim, Chul‐Hwan
Abstract : In the modern power systems, controllable loads are integrated through demand response (DR) programs and energy storage systems are exploited to provide virtual inertia (VI) with the help of power converters. The effectiveness of DR and VI in improving the power system's performance is well‐addressed in the literature, however, their impact on the power system's stability is not well‐documented. In this work, a novel analytical model is developed for sensitivity and stability analysis of power system frequency response with respect to important system parameters considering DR and VI. The developed model considers the individual and combined role of DR and VI control loops in the power system. The model is validated through extensive simulations on different systems with slow and fast dynamics. It is shown that, despite providing better frequency response, the introduction of DR and VI control loops can sometimes deteriorate the stability margins of the power system. The findings of this study call for careful calculations during the process of integrating DR and VI controls to the conventional power system.